Control of the Outbreak of Disease Aftermath Earthquake: an Overview - Marahatta, Sujan Babu (Nepal Journal of Epidemiology, 2015)
DOI: http://dx.doi.org/10.3126/nje.v5i2.12828 Nepal J Epidemiol. 2015;5(2); 468-469.